Foreign Policy and Identity: A Contribution from a Bourdieusian-Inspired Framework of Analysis - Bárbara Vasconcellos de Carvalho Motta (Contexto Internacional)
Abstract While the knowledge that identities matter is reasonably consolidated in International Relations, the evaluation of how identities matter and how they work in setting the boundaries of political actions is still a work in progress. The present article connects this debate with International Political Sociology (IPS) by bringing Bourdieu’s concepts of habitus, field, and doxa to the analysis of identity and foreign policy, which can be used as heuristic devices to address identity without essentializing it. Hence, this article makes a twofold contribution. First, it translates Bourdieu’s concepts of habitus, field, and doxa to Foreign Policy Analysis (FPA) and shows how they help to accommodate the binary logic of agent/structure around which the debate on foreign policy and identity is structured. Second, it provides an analytical framework through which one can operationalize Bourdieu’s concepts and identify how identity is mobilized through discourses not only because it is a part of a nation’s idea of itself but also because they improve the chances of a decision-maker to guarantee approval for its foreign policy actions.